LOW AWARENESS, TARGET ORGAN DAMAGE AND CARDIOVASCULAR COMPLICATIONS OF HYPERTENSION IN LOW RESOURCE SETTING. (April 2021) - Onwubere, Basden; Ejim, Emmanuel; Ogah, Okechukwu
Abstract : Objective: This paper reviews the current picture of low awareness, target organ damage, and cardiovascular complications in Africa using available literature as well as meta-analyses. Sub-Saharan Africa typically consists mostly of a low resource setting. Figure. No caption available. Design and method: Meta-analyses of publications on hypertension and related cardiovascular complications in Africa were carried out. An extensive literature search was carried out. Publications were mainly from various locations in Sub-Saharan Africa (SSA). Results: A meta-analysis of 37 publications showed the prevalence of hypertension varied extensively between and within studies. Prevalence was higher in urban than in rural populations; it was also higher with increasing age in most studies. Less than 40% were previously diagnosed. Of these less than 30% were on drug treatment, and less than 20% had blood pressure within the defined normal range. Ogah and Rayner identified 38 publications from Sub-Saharan Africa mostly conducted in urban areas: two national surveys (Malawi and Mozambique), 14 in rural settings, 16 in urban communities, one each in semi-urban and semi-urban/rural settings, and four in both rural and urban communities (figure 1) The treatment status for South African black males with hypertension showed that 20% were aware of their condition, 14% of them were on treatment and only 7% were controlled. ; these figures were respectively 47%, 29%, and 15% for women (Steyn et al) Of 219 hypertensives, in a population in Ghana 104 (47.5%) had evidence of target organ damage. Other studies from Tanzania, Sudan, South Africa, and Nigeria showed a significantly low level of Awareness, significant Target Organ Damage mostly at the time of diagnosis. Generally in Nigeria and most, some other African countries, complications of hypertension contributes significantly to Hospital admissions (Onwubere et al) Conclusions: It is observed that in most parts of Africa, hypertension presents with earlier and more severe target organ damage compared to developed country settings. This results from the late presentation, ignorance of the need for regular medical checks, paucity of adequate medical facilities, poverty, sub-standard drugs, and ethnic and genetic factors.